AERMOD Modeling Analysis of CO And Nox Parameters From Diesel Generator Emission Sources in the Coal Mining Industry - Pandu Sapta Nugraha; Arum Setiawan; Indra Yustian (Sriwijaya Journal of Environment, 2023)
Regulation of the Minister of Environment and Forestry of the Republic of Indonesia No. 4 of 2021: All types of businesses and activities must manage environmental impacts. Emissions resulting from the use of heavy equipment in the operational activities of the coal mining industry, such as scrapers, dump trucks, loaders, excavators and bulldozers. In addition to heavy equipment, exhaust emissions are generated from the use of generators that operate longer than 1,000 hours per year. The resulting emissions will have a long-term impact on air quality around business activities [1]. In an effort to tackle the spread of air pollution, modeling is carried out which aims to analyze emission air dispersion patterns by measuring exhaust emissions with Nitrogen Dioxide (NOx) and Carbon Monoxide (CO) test parameters in industrial activity areas with AERMOD applications and can predict emission air dispersion patterns dispersed into the air based on the distance and concentration of particles. One of the models used is the Gaussian Plume Model. Modeling is done by processing data from the meteorological section with AERMOD software, which will then provide a distribution pattern with a distribution pattern that is close to the true value [2]. Modeling is carried out with a radius of 5,000 meters and data from emission measurements from the power generation unit. Based on the modeling results, the CO parameter emission dispersion obtained the highest value in February with a value of 30.4 µq/m3 and the lowest value in March with a value of 3.43 µq/m3. As for the NOx parameter, the highest dispersion value was in June at 6.21 µq/m3, and the lowest value was in January at 3.51 µq/m3. This research was conducted in March 2023. It is located on the project site of the Coal Mining Industry area with a mining business permit (IUP) area of 2936.14 ha in Mekar Jadi Village, Sungai Lilin District, Musi Banyuasin Regency, South Sumatra Province.